Wpływ odłogowania gruntów na ich niektóre właściwości chemiczne, aktywność enzymatyczną oraz skład gatunkowy chwastów = The influence of allowing to rest of the recultivated land on its some physical and chemical properties, enzyme activity, as well as weed species composition - Drab, Michał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The influence of the allowing to rest of the former recultivated agricultural land on the weed species composition and changes of pH, available forms of phosphorus and potassium, organic C, total N and enzyme activity (dehydrogenase, urease, amylase and invertase) werepresented in the paper.
Keywords: 2 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: zagospodarowanie zlewni" (21-22.06.2001)